2013
DOI: 10.1103/physrevb.88.224302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of loss on the dispersion relation of photonic and phononic crystals

Abstract: A theoretical analysis is made of the transformation of the dispersion relation of waves in artificial crystals under the influence of loss, including the case of photonic and phononic crystals. Considering a general dispersion relation in implicit form, an analytic procedure is derived to obtain the transformed dispersion relation. It is shown that the dispersion relation is generally shifted in the complex (k,ω) plane, with k the wave number and ω the angular frequency. The value of the shift is obtained exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…It is found that numerical results follow closely the perturbation theory in Ref. [11], according to which the damping of a given Bloch wave can be estimated at any frequency from a volume average of the viscoelastic constituents weighted by the Bloch wave distribution. In particular, the complex-eigenfrequency band structure ω(k) does not capture any spatial propagation information but provides one with information complementary to the complex band structure k(ω).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is found that numerical results follow closely the perturbation theory in Ref. [11], according to which the damping of a given Bloch wave can be estimated at any frequency from a volume average of the viscoelastic constituents weighted by the Bloch wave distribution. In particular, the complex-eigenfrequency band structure ω(k) does not capture any spatial propagation information but provides one with information complementary to the complex band structure k(ω).…”
Section: Introductionsupporting
confidence: 75%
“…In the small damping limit, the first-order perturbation theory of Ref. [11] applies. The main result of this theory in our context is that the relative variation of the frequency of a band at a fixed value of the Bloch wavevector is given by…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in this process we also calculate the exceptional point (EP)-the point at which the spectrum of the perturbed assembly has a non-Hermitian degeneracy, where two of its eigenmodes coalesce, together with their corresponding complex frequencies [26][27][28]. This occurs in our example for an assembly comprising a lossy slab with specific viscoelastic shear modulus [29].…”
Section: Introductionmentioning
confidence: 99%
“…For frequency-dependent systems, the estimation of the group velocity is not trivial. 38,39 Equation 4 is differentiated and multiplied by the left eigenvector ψ l i T following the procedure proposed by 38 such that…”
Section: Group Velocitymentioning
confidence: 99%